Front Cover: Real‐Time Observation of Diarylethene‐Based Photoswitches in a Cyclic Peptide Environment (ChemPhotoChem 6/2019). Issue 6 (13th June 2019) - Schweigert, Caroline; Babii, Oleg; Afonin, Sergii; Schober, Tim; Leier, Julia; Michenfelder, Nadine C.; Komarov, Igor V.; Ulrich, Anne S.; Unterreiner, Andreas Neil
Abstract : The Front Cover illustrates diarylethene‐based photoswitches incorporated into macrocyclic peptides with variable ring sizes. The Jablonski diagram shows possible relaxation pathways after photoexcitation, with triplet absorption dominating the entire visible spectral window in all cases. The fluorescence intensity was found to increase with smaller ring sizes, resulting in less efficient ring closure. (This project was made possible by collaboration within the GRK 2039 "Molecular architecture for fluorescent cell imaging" plus additional funding from the EU and BMBF). More information can be found in the Article by C. Schweigert et al. on page 403 in Issue 6, 2019 (DOI: 10.1002/cptc.201900005 ).